Etika Profesi Guru Pendidikan Anak Usia Dini - Zherly Nadia Wandi; Nurhafizah Nurhafizah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2019)
AbstractThis study aims to determine the professional ethics of early childhood education teachers in kindergartens in Padang Timur Subdistrict, Padang City. This study uses descriptive methods that are analytical. Respondents involved included teachers and principals. For the target population in this study were kindergarten teachers in Padang Timur District, Padang City in 5 Kindergarten Institutions with 41 samples. Data collection is done through observation or observation, interviews, and documentation. The results of the study indicate that in early childhood education teacher ethics, based on Republic of Indonesia Law Number 14 of 2005 concerning Teachers and Lecturers also Decision of the XXI Congress of the Republic of Indonesia Teacher Association Number: Vi / Congress / Xxi / Pgri / 2013 concerning Teacher Ethics Code Indonesia with its research focus, namely: The obligation of teachers to students; Obligations of teachers to parents or guardians of students; The obligation of teachers to colleagues indicates that teacher professional ethics are in accordance with those carried out in the field, but must be further optimized in its application.Keywords: Teacher Professional Ethics, Early Childhood Education.       AbstrakPenelitian ini bertujuan untuk mengetahui etika profesi guru pendidikan anak usia dini di taman kanak-kanak di Kecamatan Padang Timur, Kota Padang. Penelitian ini menggunakan metode deskriptif yang bersifat analitik. Responden yang terlibat termasuk guru, dan kepala sekolah. Untuk populasi target dalam penelitian ini adalah guru TK di Kabupaten Padang Timur, Kota Padang di 5 Lembaga TK dengan 41 sampel. Pengumpulan data dilakukan melalui observasi atau pengamatan, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa dalam etika guru pendidikan anak usia dini, berdasarkan Undang-Undang Republik Indonesia Nomor 14 Tahun 2005 tentang Guru dan Dosen juga Keputusan Kongres XXI Republik Indonesia Asosiasi Guru No. Nomor: Vi / Kongres / Xxi / Pgri / 2013 tentang Kode Etik Guru Indonesia dengan fokus penelitiannya, yaitu:  Kewajiban guru kepada siswa; Kewajiban guru kepada orang tua atau wali murid; Kewajiban guru kepada kolega menunjukkan bahwa etika profesi guru sesuai dengan yang dilakukan di lapangan, tetapi harus lebih dioptimalkan dalam penerapannya.Kata Kunci: Etika Profesi Guru, Pendidikan Anak Usia Dini.